Evaluation of interstitial cells of Cajal in patients with severe colonic inertia requiring surgery: a clinical‐pathological study. (May 2017) - Cohen, M.; Cazals‐Hatem, D.; Duboc, H.; Sabate, J.‐M.; Msika, S.; Slove, A. L.; Panis, Y.; Coffin, B.
Abstract: Aim: Subtotal colectomy is the treatment of last resort in patients with severe colonic inertia (SCI) refractory to laxatives. Some studies have reported hypoplasia of the interstitial cells of Cajal (ICC) using a semi‐quantitative analysis. The aims of this study were first to investigate if semi‐quantitative analysis or morphometry is better at the quantification of colonic ICC and second to determine whether there is a relationship between the number of ICC and the severity of constipation. Method: Clinical and pathological data from patients with subtotal colectomy for SCI were collected. Quantification of ICC using CD117 immunohistochemistry and morphometric methods was performed at three different colonic sites in patients and controls. Results: Twenty patients had a colectomy for SCI. All were considered to have failed maximal medical treatment and 45% were hospitalized at least once for colonic obstruction due to faecaloma. Using a semi‐quantitative methodology, 30% of patients displayed ICC hypoplasia (< 7 per high power field) and all controls had normal ICC. Using morphometry, the percentage of colonic ICC was significantly less in patients compared with controls with no significant differences between the ascending, transverse and descending colonic segments. Overall 60% of patients had ICC hypoplasia (< 1% vs 20% of controls, P  =   0.009). The severity of constipation was not related to the quantity of ICC. Conclusion: In patients with SCI, morphometric analysis is more sensitive than semi‐quantitative analysis in the detection of ICC hypoplasia. The severity of constipation was not related to the quantity of ICC.